Fast food landscapes: Exploring restaurant choice and travel behavior for residents living in lower eastside Detroit neighborhoods. (December 2017) - Eckert, Jeanette; Vojnovic, Igor
Abstract: As the U.S. battles a public health crisis centered on obesity and diet-related diseases, the role of urban foodscapes and available food outlets on choice and consumption is an area of research interest. Restaurant dining provides opportunities for consumption of excessive calories, especially when healthful alternatives are not on the menu. This study analyzes the results of a travel survey in Detroit to examine a) the frequency of restaurant dining, b) the proportion of restaurant dining which is fast food, c) travel behavior including mode of travel and distance traveled. Sixty percent of respondents reported traveling to a restaurant at least once per week, and the majority of those trips were to nearby fast food restaurants. We found that more frequent restaurant dining was related to a higher BMI and the presence of children in the home, and that respondents with higher incomes were more likely to travel farther outside the neighborhood to seek out preferred dining locations. The findings suggest lower income residents may be more susceptible to the available options in the neighborhood than those with higher incomes and/or greater mobility. Highlights: Sixty percent of respondents reported traveling to a restaurant at least once per week. The majority of trips were to nearby fast food restaurants. More frequent restaurant dining was related to a higher BMI and the presence of children in the home. Respondents with higher incomes and those with access to a vehicle were more likely to travel farther to restaurants. Lower income residents may be more limited to the options in the neighborhood than those with higher incomes and/or mobility.